A critical exploration of institutional logics of de-institutionalisation in the field of disability policy and practice: Towards a socio-spatial professional orientation - Griet Roets; Matthias Remmery; Dries Cautreels; Simon Allemeersch; Toon Benoot; Rudi Roose (Social Work and Society)
This contribution throws light on how historical as well as contemporary interpretations of 'de-institutionalisation' in the institutional field of disability policy and practice have transformed over time and place/context, yet continue to be essentially ambiguous and contested. We address that the current 'community turn' has gradually produced a problematic dichotomy in disability policy and practice between 'segregated living in residential, institutional contexts' being framed as something to avoid, and 'inclusive living in the community' as a desirable goal. We suggest that a socio-spatial professional orientation might enable us to de-institutionalise this dominant dichotomy.